Soft Skills Nurturing Altruistic Leaders - Hadijah, Ahmad; Fatmawati, Latada; Siti Fatihah, Ghazali; Ahmad Muhaimin, Mohamad; Mohd Rahimi, Ramli (Centre for Human Sciences, UMP, 2022)
Soft skills have become one of the university’s compulsory subjects in an effort to nurture holistic students who are not only excellence in knowledge and skills but also possess good personality. Therefore, the topics discuss in this book are spiritual intelligence, emotional intelligence, manners and positive values as a leader in terms of communication and attitude in daily life and at work place.